Analisis Kedaruratan K3 dengan Kejadian Kecelakaan pada Proyek Konstruksi Bangunan di Perumahan Grand Safira Binjai - Annisa Latifah Salsabila; Dinda Muhajirina; Oppy Oktavianty Windari; Abdurrozzaq Hasibuan (Institute of Advanced Knowledge and Science, 2024)
Occupational Safety and Health (K3) is a very important aspect in every construction project, especially in residential environments that involve building construction activities. Work accidents are a serious problem that can have a direct negative impact on workers, the surrounding environment and the project as a whole. Therefore, K3 emergency analysis is crucial for identifying potential accidents and formulating appropriate mitigation measures. The aim of this research is to find out what K3 emergencies are related to accidents during building construction at the Grand Safira Binjai housing complex. The writing method used is a quasi-experimental method, namely by giving a pre-test and post-test to measure the level of success of the research carried out and provide counseling. The results of the research show that the K3 emergency analysis with accidents on the building construction project at the Grand Safira Binjai housing complex is an increase in workers' knowledge about the work environment from initially 57.2% to 94.4% and an increase in workers' knowledge about the use of Personal Protective Equipment ( PPE) which was initially 39.8% became 85.2%. By increasing worker awareness and knowledge regarding Occupational Safety and Health (K3), it is hoped that a safer work environment can be created, increase productivity, and reduce costs due to accidents and work illnesses.